Acroteriobatus omanensis (Batoidea: Rhinobatidae), a new guitarfish from the Gulf of Oman - Last, Peter R.; Henderson, Aaron C.; Naylor, Gavin J.p. (Zootaxa, 2016)
The recently resurrected genus Acroteriobatus is represented in the western Indian Ocean by eight species, including a new guitarfish Acroteriobatus omanensis sp. nov. This small species (reaching 60 cm TL) was discovered off Oman in an investigation of the chondrichthyan fauna of the Arabian in 2002 and 2003. Its distinctiveness from other members of the genus Acroteriobatus is strongly supported by molecular data. Acroteriobatus omanensis sp. nov. differs from all other members of the genus by its very narrowly pointed snout and having a dense pattern of small, symmetrically arranged ocelli each consisting of a white spot surrounded by a darker rim. Acroteriobatus annulatus and A. ocellatus have a more-or-less ocellated dorsal colour pattern but the markings are larger and differ in form (ocelli consisting of a small dark central spot surrounded by a dark-edged pale ring in A. annulatus; larger, irregularly shaped ocelli with pale centres surrounded by a dark brown rim in A. ocellatus).